Ukraine : Request for Stand-By Arrangement and Cancellation of Current Arrangement Staff Report; Staff Supplement; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
Even though the global financial crisis hit Ukraine hard, the Stand-By Arrangement (SBA) program managed to restore macroeconomic and financial stability. Executive Directors welcomed the new SBA aimed to consolidate public finances, restore banking system soundness, and develop a more robust monetary policy framework. Directors stressed the need for implementing tax and expenditure policies, pension reforms to catalyze financing, and measures to strengthen the banking system. Directors advised that strict adherence to these policies will help deepen market access, facilitating exit from IMF financial support.